Spatial and phylogenetic distribution of the genera of the Heliantheae tribe (Asteraceae) in Mexico - Luis Morales-Garduño; José Luis Villaseñor (Botan‪ical Sciences)
Background: Biodiversity is described considering its alpha (local taxon richness), beta (difference of taxa between localities), or gamma (regional richness) components. We assessed the alpha component using different facets, taxonomic and phylogenetic. In Mexico, more than half of the genera of the Heliantheae tribe are included in a phylogeny, and a taxonomically curated geographic database is available, facilitating their study under these concepts.